Planning and Record Keeping of Educational Work Done by Professional and Teaching Staff While Implementing Distance Learning Training Programs - V. Sviridenko, O.; Y. Bauer, V.; A. Baluyeva, Y.; V. Komerzan, E. (International Journal of Engineering and Technology, 2018)
Organization of the educational process includes planning teachers’ work carried out while implementing BPEP in distance learning form. An important objective of this stage is to identify certain types of teachers’ work that differ from the classroom and their rationing. At the Russian universities, the planning system has been used for more than half a century, however, the emergence of new teaching technologies requires making significant changes to it. The article describes the educational work planning process done by the professional and teaching staff of "NRU" MPEI" carried out while implementing educational programs with distant education technologies; certain types of teachers’ work were found out and standard time to accomplish them was set.